IOT Based Automatic Counters For Classroom Capacity In The New Normal Era Of Covid-19 - Pracasitaram, I Gede Made Surya Bumi; Ratnaya, I Gede (Prahasta Publisher, 2022)
This study aims to design and develop a prototype of a program for automatic classroom capacity counters in the new normal era of COVID-19. The prototype consists of an ultrasonic sensor to detect students who are entering and out from the classroom, a microcontroller as a data processor from sensor readings, and output is the number of students who are in the room, displayed on an LCD and can be monitored remotely with an IOT (Internet of Things) system. This study employs Research and Development approach, consisting of several stages covering information collection, continued by designing and developing the prototypes, testing and repairing the tools. From the test, the developed prototype function properly, the counter results in the LCD display has 100% of conformity, and the display on the Blynk Web Application results in 75% of confirmity.